Massaad's question via email about Laplace Transforms

In summary, the solution to the initial value problem using Laplace Transforms is $\displaystyle y\left( t \right) = \left[ 21 - 3\,\mathrm{e}^{6\,\left( t - 6 \right) } - 18\,\mathrm{e}^{-\left( t - 6 \right) } \right] \, H\left( t - 6 \right) - 5\,\mathrm{e}^{-t}$.
  • #1
Prove It
Gold Member
MHB
1,465
24
$\displaystyle y\left( t \right)$ satisfies the initial value problem:

$\displaystyle \frac{\mathrm{d}^2y}{\mathrm{d}x^2} - 5\,\frac{\mathrm{d}y}{\mathrm{d}t} - 6\,y = -126\,H\left( t - 6 \right) , \quad y\left( 0 \right) = -5, \,\, y'\left( 0 \right) = 5$

Find the solution to the initial value problem using Laplace Transforms.

Taking the Laplace Transform of the equation gives

$\displaystyle \begin{align*} s^2\,Y\left( s \right) - s\,y\left( 0 \right) - y'\left( 0 \right) - 5\left[ s\,Y\left( s \right) - y\left( 0 \right) \right] - 6\,Y\left( s \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s} \\
s^2\,Y\left( s \right) - s\left( -5 \right) - 5 - 5 \left[ s\,Y\left( s \right) - \left( -5 \right) \right] - 6\,Y\left( s \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s} \\
s^2\,Y\left( s \right) + 5\,s - 5 - 5\,s\,Y\left( s \right) - 25 - 6\,Y\left( s \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s} \\
\left( s^2 - 5\,s - 6 \right) Y\left( s \right) + 5\,s - 30 &= -\frac{126\,\mathrm{e}^{-6\,s}}{s} \\
\left( s - 6 \right) \left( s + 1 \right) Y\left( s \right) + 5 \left( s - 6 \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s} \\
\left( s + 1 \right) Y\left( s \right) + 5 &= -\frac{126\,\mathrm{e}^{-6\,s}}{s\left( s - 6 \right) } \\
\left( s + 1 \right) Y\left( s \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s\left( s - 6 \right) } - 5 \\
Y\left( s \right) &= -\frac{126\,\mathrm{e}^{-6\,s}}{s\left( s - 6 \right) \left( s + 1 \right) } - \frac{5}{s + 1}\end{align*}$

The second term is easy to find the inverse transform of: $\displaystyle \mathcal{L}^{-1}\,\left\{ \frac{5}{s + 1} \right\} = 5\,\mathrm{e}^{-t} $.

For the first term, due to the exponential function, it suggests a second shift: $\displaystyle \mathcal{L}\,\left\{ f\left( t - a \right) \,H\left( t - a \right) \right\} = \mathrm{e}^{-a\,s}\,F\left( s \right) $.

So in this case, we have $\displaystyle F\left( s \right) = -\frac{126}{s\left( s - 6 \right) \left( s + 1 \right) } $.

To find $\displaystyle f\left( t \right) $ we will need partial fractions:

$\displaystyle \begin{align*} \frac{A}{s} + \frac{B}{s - 6} + \frac{C}{s + 1} &\equiv \frac{-126}{s\left( s - 6 \right) \left( s + 1 \right) } \\
A \left( s - 6 \right) \left( s + 1 \right) + B\,s\left( s + 1 \right) + C\,s \left( s - 6 \right) &\equiv -126 \end{align*} $

Let $\displaystyle s = 0 \implies -6\,A = -126 \implies A = 21$

Let $\displaystyle s = 6 \implies 42\,B = -126 \implies B = -3$

Let $\displaystyle s = -1 \implies 7\,C = -126 \implies C = -18 $

So

$\displaystyle \begin{align*} F\left( s \right) &= 21 \left( \frac{1}{s} \right) - 3 \left( \frac{1}{s - 6} \right) - 18 \left( \frac{1}{s + 1} \right) \\
f\left( t \right) &= 21 - 3\,\mathrm{e}^{6\,t} - 18\,\mathrm{e}^{-t} \end{align*}$

Thus $\displaystyle \mathcal{L}^{-1}\,\left\{ -\frac{126\,\mathrm{e}^{-6\,s}}{s\left( s - 6 \right) \left( s + 1 \right) } \right\} = \left[ 21 - 3\,\mathrm{e}^{6\,\left( t - 6 \right) } - 18\,\mathrm{e}^{-\left( t - 6 \right) } \right]\,H\left( t - 6 \right) $ by the second shift theorem.

So now we can finally write the solution to the DE:

$\displaystyle y\left( t \right) = \left[ 21 - 3\,\mathrm{e}^{6\,\left( t - 6 \right) } - 18\,\mathrm{e}^{-\left( t - 6 \right) } \right] \, H\left( t - 6 \right) - 5\,\mathrm{e}^{-t}$
 
Mathematics news on Phys.org
  • #2


I hope this helps answer your question, Massaad. Let me know if you have any further questions or if anything is unclear. Keep up the good work with Laplace Transforms!
 

Similar threads

Replies
2
Views
10K
Replies
1
Views
10K
Replies
1
Views
10K
Replies
1
Views
10K
Replies
4
Views
10K
Replies
1
Views
10K
Replies
1
Views
9K
Replies
1
Views
10K
Back
Top